2020
DOI: 10.3390/electronics9061027
|View full text |Cite
|
Sign up to set email alerts
|

Sizing CMOS Amplifiers by PSO and MOL to Improve DC Operating Point Conditions

Abstract: The sizes of the metal-oxide-semiconductor (MOS) transistors in an operational amplifier must guarantee strong direct current operating point (DCOP) conditions. This paper shows the usefulness of two population-based optimization algorithms to size transistors, namely—particle swarm optimization (PSO) and many optimizing liaisons (MOL). Both optimization algorithms link the circuit simulator SPICE to measure electrical characteristics. However, SPICE provides an output-file indicating that a transistor is in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…Note that different objective functions and constraints other than ( 7) can be used. For example, [28] defines a new kind of Figure of Merit. ESSAB applies to any objective functions and constraints.…”
Section: Experimental Results and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that different objective functions and constraints other than ( 7) can be used. For example, [28] defines a new kind of Figure of Merit. ESSAB applies to any objective functions and constraints.…”
Section: Experimental Results and Comparisonsmentioning
confidence: 99%
“…Instead, it aims at addressing the above two key challenges when introducing machine learning techniques into optimization-based analog IC sizing. Important research topics such as sizing problem definition assessing the merit of designs, yield optimization considering process, voltage and temperature variations [28] are out of the scope but compatible with ESSAB.…”
Section: The Essab Methodsmentioning
confidence: 99%
“…For instance, the OTAs require high differential gain, high gain-bandwidth product, and the best linearity as possible [34]. In addition, an OTA must be robust to PVT and Monte Carlo variations [35]. This section details the design of the blocks required to implement the proposed OTA-based FOCO 1 shown in Figure 6 and FOCO 2 shown in Figure 8, by using CMOS technology of 180 nm from UMC.…”
Section: Cmos Design Of the Otas Multiplier Nonlinear Function And Fractional-order Integratormentioning
confidence: 99%
“…The sizes of the CMOS OTA, to provide a gm = 500 µA/V and gm = 350 µA/V, are shown in Table 1 by using a load capacitor of C L = 220 pF. The table lists the direct current (DC) gain in decibels (dB), gain-bandwidth (GBW) in kilo hertz (KHz), phase margin (PM) in degrees ( • ), common-mode rejection ration (CMRR) in dB, slew rate (SR) in volt/ µs, power supply rejection ratio (PSRR), power dissipation in milliwatts, the small and large-signal figures of merit (FoM) from [35], the width (W) and length (L) of the MOS transistors in micro-meters, and the bias current (Ib).…”
Section: Cmos Operational Transconductance Amplifier (Ota)mentioning
confidence: 99%
“…Zhao et al then showed the reciprocal characterization of time series and multilayer networks and introduced the concept of interlayer entropy between two quantities aimed at measuring the strength of interrelationships from one layer to another, demonstrating that in networks it is the equivalent of transfer entropy in time series [ 10 ]. In telecommunication and electronics, integrated circuits and their design [ 11 ], both due to the wide range of dynamics that can be explored and to the huge amount of complex data that can be produced, represent an interesting field of research for many applied oriented studies like chaos-based secure communications [ 12 ] using the so called snap circuits.…”
Section: Multiple Causality Between Time Seriesmentioning
confidence: 99%